2009
DOI: 10.1007/s10640-009-9288-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Demand for Sicilian Regional Parks: A Compound Poisson Approach

Abstract: Incomplete demand system, Compound poisson, Count model, Travel cost, Q26, C35,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
2
0
1
Order By: Relevance
“…This is also confirmed by other studies on the leisure value of areas with natural value in Europe, the CS of which ranged from EUR 0.66 (Glück and Kuen 1977) to EUR 111.98 (Luttman and Schröder 1995, Zandersen and Toll 2009. This is also confirmed by research on the value of the CS in Italy, which ranged from 0.9 EUR/day in the Dolomiti Bellunesi National Park to 39.84 EUR/day in Abetina Reale (Gatto 1998) and the Madonna Park (Signorello at al. 2009, De Salvo andSignorello 2015).…”
Section: Discussionsupporting
confidence: 63%
“…This is also confirmed by other studies on the leisure value of areas with natural value in Europe, the CS of which ranged from EUR 0.66 (Glück and Kuen 1977) to EUR 111.98 (Luttman and Schröder 1995, Zandersen and Toll 2009. This is also confirmed by research on the value of the CS in Italy, which ranged from 0.9 EUR/day in the Dolomiti Bellunesi National Park to 39.84 EUR/day in Abetina Reale (Gatto 1998) and the Madonna Park (Signorello at al. 2009, De Salvo andSignorello 2015).…”
Section: Discussionsupporting
confidence: 63%
“…A meta-analysis including 265 estimates of daily CS based on 46 primary studies in Italy reported a mean CS per visit of €9.69 (in 2013 prices), with values in the range of €0.90-63.24, which are generally in the range of our results albeit with an average CS which is around three times lower. We under or overestimate the CS value for some parks, Etna for example, where previous results returned a consumer surplus value of €31.25 per trip which is around twice that found in our analysis (€16.32 per trip) (Signorello et al, 2009).…”
Section: Recreation Valuation Estimates For Italian Protected Areascontrasting
confidence: 72%
“…Value estimates based on TCM using geotagged photographs from Flickr have been shown to return value estimates for nature-based recreation which are similar to those obtained using representative surveys (Sinclair et al, 2020b). Although we cannot directly compare the value estimates presented here to results based on primary surveys, owing to a lack systematic valuation data for the study sites, we can look to past valuations for some natural sites in Italy as a comparison (Signorello et al, 2009;De Salvo and Signorello, 2015). A meta-analysis including 265 estimates of daily CS based on 46 primary studies in Italy reported a mean CS per visit of €9.69 (in 2013 prices), with values in the range of €0.90-63.24, which are generally in the range of our results albeit with an average CS which is around three times lower.…”
Section: Recreation Valuation Estimates For Italian Protected Areassupporting
confidence: 51%